The Gender Specificities Of Views About Happiness in The Structure of the Lifestyle of The Student Youth - YagnyukYa. К. (Psychiatry, Neurology and Medical Psychology, 2015)
The article shows that happiness as an important component of students’ life and its prerequisites are the compliance of value system, the importance of values’ actualization and preserving and availability of sense of life. It was found out that the psychological understanding of happiness diff ers according to gender specifi cities. In particular, young women possess two concepts of happiness: «happiness as sense of life» and «happiness as realization of values». The former, «happiness as sense of life» is sensible and presupposes a certain degree of self-dissatisfaction of young women. The second concept of happiness by both young women and young men is connected with realization of their values that is why this concept is called «happiness as realization of values».